Android-based English education application - gayatri, jesyca putri; Rafdhi, Faiz (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2022)
Current technological developments continue to be rapid and science continues to advance, requiring guidance as an educational medium. Learning education will be easier to teach to elementary school children. Educational content is highly preferred by android users. Learning media always face developments along with rapid technological developments. The MDLC method is a suitable method for designing and improving a media application which is a combination of photo, sound, video, animation and other media. The MDLC method has six stages as follows: Concept, Design, Material Collecting, Assembly, Testing and Distribution. Android-based educational applications can only be used by Android-based mobile phones. And to learn educational applications as an Android-based learning media is easier, more practical, and efficient. It is hoped that educational applications as learning media for elementary school children can help in mastering and pursuing each of the subjects contained.